UPAYA PENCEGAHAN DAN PENGENDALIAN PENYAKIT HIPERTENSI PADA LANSIA - Herwansyah; novita, willia; Fitri, Adelina; Nuzulul Putra, Ashar; Istarini, Attiya (Universitas Jambi, 2024)
Hypertension is a disease that is often experienced by older people. Some factors that can cause hypertension include obesity, unhealthy lifestyles and lack of physical activity. Various efforts have been made but hypertension is still the highest disease in every health centre in Jambi City. This service activity aims to educate the elderly to have knowledge about hypertension and implement a healthy lifestyle so that blood pressure can be controlled. Previous research has revealed that ergonomic exercises have a positive impact on controlling blood pressure. Activities that will be carried out in this service include providing education about hypertension and healthy lifestyles, health checks, and implementing ergonomic exercises. After educational activities and routine gymnastics every week, it is known that blood pressure in the elderly who take part in this activity becomes controlled. It is hoped that gymnastic activities and education about hypertension will be carried out regularly so that the health of the elderly will be better.